Os processos incorporativos do indígena kaingang de Atalaia à sociedade luso-brasileira : o papel do Catolicismo - Durat, Cristiano Augusto (2006)
This study has the premise to reconstruct the relations established between the Indigenous Kaingang and the Portuguese settlers in the beginning years of occupation of the Guarapuava Plato, a territory, in the south west of Captaincy of Sao Paulo, during the years of 1812 1828. The article points at the historical aspects, noted by the proper society, involved in the process of colonialism, and by the residing chroniclers. It shows the means used by the missionaries, including the pedagogic and symbolic aspects, in exercising their missionary functions, among the indigenous Kaingang. The study permits a greater comprehension of the strategies used, and the situations lived by the groups. The primary element that permitted the reconstruction of these historical and cultural aspects, was, the Sacramental Register Book, which contains baptismal and marriage registers, also the Book of Obits. The econstruction of these relationships proportioned us a new direction, to visualize the process of Portuguese expansion in the Indigenous Kaingang territory